The state and development of research in the field of gifted education over 60 years: A bibliometric study of four gifted education journals (1957–2017). (2nd July 2020) - Hernández-Torrano, Daniel; Kuzhabekova, Aliya
ABSTRACT: The field of gifted education emerged in 1920s. Since that time, it has evolved from an emerging research area to a relatively mature field with regular regional and international conferences and key journals publishing main theoretical developments and empirical explorations in the field. This descriptive bibliometric study examines the state and development of international research on gifted education using publication and citation data from four specialized journals in the field between 1957 and 2017. The study reveals the dynamics of publication and citation on gifted education research over time, as well as the distribution of articles across the four journals. The analysis also provides an idea of the countries/regions and institutions leading the research on gifted education and information about the most productive authors, as well as the most influential articles over the last 60 years. In addition, the study uncovers the snapshot of collaboration networks between countries/regions, institutions, and individual researchers. Finally, the findings about the state and development of research on gifted education are discussed and the implications for the development of the field are presented.